Partial substitution of cement by the association of Ferronickel slags and Crepidula fornicata shells. (January 2021) - Bouasria, Manal; Khadraoui, Fouzia; Benzaama, Mohammed-Hichem; Touati, Karim; Chateigner, Daniel; Gascoin, Stéphanie; Pralong, Valérie; Orberger, Beate; Babouri, Laidi; El Mendili, Yassine
Abstract: Environmental impacts of building materials can be achieved by reducing the amount of cement in cementitious composites, specifically when incorporating wastes as partial replacement of Portland cement. In this work we substitute cement by shell by-products and Ferronickel Slags (FNS) while keeping interesting specific properties. FNS associated to Crepidula fornicata shells (CR) are good candidates to replace part of the Portland cement as they have appropriate physicochemical properties, and are available at high abundance. The effect of the association of FNS and CR on the mechanical properties of mortar is investigated. Microstructural characterization of these additives are carried out using Scanning Electron Microscopy, X-Ray diffraction and Raman spectroscopy. Formulated mortars contain different mixes of FNS-CR and Portland cement. Specific surface area, workability and setting times of fresh mortars are studied. The mechanical properties are investigated using 3-point bending and compressive tests for curing periods ranging from 2 to 28 days. In the fresh state, the replacement of cement by up to 20 wt.% of FNS-CR does not significantly affect mortar properties. However, at the hardened state, the setting time is increased using FNS-CR. With up to 20% wt.% of FNS-CR incorporation, the mechanical properties are similar or even slightly larger than that of the control mortar. Highlights: FNS and CR shells show their potentials as supplementary material for Portland cement. FNS and CR shells can replace Portland cement with equivalent mechanical properties. FNS and CR improves the mechanical strengths more at early age. For a cement substitution by FNS, a rate up to 10% led to the best mortar behavior. For a cement replacement by FNS-CR, a rate up to 20% led to the best mortar behavior.